Mutation of Drosophila homer disrupts control of locomotor activity and behavioral plasticity. - Diagana, T.T.; Thomas, U.; Prokopenko, S.N.; Xiao, B.; Worley, P.F.; Thomas, J.B. (Journal of Neuroscience, 2002)
Homer proteins have been proposed to play a role in synaptogenesis, synapse function, receptor trafficking, and axon pathfinding. Here we report the isolation and characterization of the Drosophila gene homer, the single Homer-related gene in fly. Using anti-Homer antibody we show that Homer is expressed in a broad range of tissues but is highly enriched in the CNS. Similarly to its mammalian counterpart, the Drosophila Homer localizes to the dendrites and the endoplasmic reticulum (ER). This subcellular distribution is dependent on an intact Enabled/Vasp homology 1 domain, suggesting that Homer must bind to one or more of its partners for proper localization. We have created a mutation of homer and show that flies homozygous for this mutation are viable and show coordinated locomotion, suggesting that Homer is not essential for basic neurotransmission. However, we found that homer mutants display defects in behavioral plasticity and the control of locomotor activity. Our results argue that in the CNS, Homer-related proteins operate in the ER and in dendrites to regulate the development and function of neural networks underlying locomotor control and behavioral plasticity.